Upaya Pencegahan Stunting Melalui Penyuluhan dan Pemberian Makanan Tambahan Pada Ibu Hamil - Zaman, Maulidia Bintang Nur; Sari, Ira Puspita; Wahyudi, Catur; Susilawati, Agnes Dwita; Amin, Mohammad Arridho Nur; Yunita, Eva Anggra; Sulistyani, Tri (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2025)
The problem of stunting is a crucial issue that must be addressed collectively. Poverty and low levels of knowledge are key factors that must be addressed to prevent stunting. Stunting prevention must be implemented as early as possible, starting from when the fetus is still in the womb. A child's first 1,000 days must be protected. To reduce stunting rates, collaboration between the government, health services, social services, and the wider community is crucial. One way to reduce stunting is by raising awareness of stunting through outreach and mentoring. The community service program was implemented by the Lambanggelun Village Community Service Team in collaboration with the Paninggaran District Health Center and the Lambanggelun Village government. Lambanggelun Village, Paninggaran District, is one of the villages with a high stunting rate. The activity began with an FGD. The FGD results showed that the Lambanggelun Village community still has low knowledge and awareness of stunting prevention. Therefore, the Lambanggelun Village Community Service Team began its activities with data collection to obtain the latest data on the number of pregnant women in Lambanggelun Village. The data collection results showed that there were 20 pregnant women. After the data collection, the program continued with the preparation of materials, the creation of educational videos, the educational process, and finally, evaluation and provision of supplementary food for pregnant women. The results of the educational activities showed that pregnant women became more aware of the dangers of stunting and there was an increase in their own prevention efforts.